2021
DOI: 10.3390/s21041361
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Fluid Retention in Patients with Advanced Heart Failure: A Review of a Novel Multisensory Algorithm, HeartLogicTM

Abstract: Heart failure (HF) hospitalisations due to decompensation are associated with shorter life expectancy and lower quality of life. These hospitalisations pose a significant burden on the patients, doctors and healthcare resources. Early detection of an upcoming episode of decompensation may facilitate timely optimisation of the ambulatory medical treatment and thereby prevent heart-failure-related hospitalisations. The HeartLogicTM algorithm combines data from five sensors of cardiac implantable electronic devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Previously, CIED-based single sensor impedance measurements were not robust enough to detect impending fluid retention (17)(18)(19). Overcoming many of the drawbacks of its predecessors, the HeartLogic TM algorithm combines five pathophysiological CIED-based sensors: the first and the third heart sounds (S1 and S3, respectively) and the ratio of S3/S1, respiration rate, intrathoracic impedance, night heart rate and physical activity to detect impending fluid retention (8,9). A study from Calò et al confirmed that CIED measured heart sounds can accurately detect systolic and diastolic left ventricular functional impairment (20) et al demonstrated that all individual sensor values of the HeartLogic TM algorithm deviated significantly prior to an event of decompensated heart failure (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, CIED-based single sensor impedance measurements were not robust enough to detect impending fluid retention (17)(18)(19). Overcoming many of the drawbacks of its predecessors, the HeartLogic TM algorithm combines five pathophysiological CIED-based sensors: the first and the third heart sounds (S1 and S3, respectively) and the ratio of S3/S1, respiration rate, intrathoracic impedance, night heart rate and physical activity to detect impending fluid retention (8,9). A study from Calò et al confirmed that CIED measured heart sounds can accurately detect systolic and diastolic left ventricular functional impairment (20) et al demonstrated that all individual sensor values of the HeartLogic TM algorithm deviated significantly prior to an event of decompensated heart failure (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, CIEDs also allow for continuous monitoring of a range of physiological parameters through various sensors. The recently developed CIED based algorithm HeartLogic TM (Boston Scientific St. Paul, United States) uses five sensors to detect impending fluid retention (8,9). These five sensors assess the first and the third heart sounds (S1 and S3, respectively) and the S3/S1ratio, respiration rate, intrathoracic impedance, night heart rate and physical activity (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote monitoring allows early recognition of technical issues (such as lead failure, battery depletion, programming issues including insufficient margins for sensing or capture) as well as early detection of arrhythmias [ 26 , 27 ]. Furthermore, several CIED types may provide comprehensive information on worsening heart failure and thereby conceptually prevent heart failure hospitalisations [ 28 , 29 ]. The current results support the previously described effectiveness of remote monitoring in lowering hospitalisation and mortality rates [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Some of the most prominent and promising devices include CardioMEMS Heart Failure System, HeartPOD (Abbott), HeartLogic (Boston Scientific), V-LAP (Vectorious Medical Technologies), Medtronic OptiVol Fluid Status Monitoring and CareLink Network (OptiLink Heart Failure), and Chronicle IHM (Medtronic). [14][15][16][17][18][19][20] However, many of these TM technologies are invasive and require patient adherence, typically for the transfer of patientinitiated sensor data to an internet-connected device. 17 Previous studies have reported high adherence rates, but it should be noted that these studies typically exclude patients who are non-adherent with TM or disinclined to participate due to onerous trial protocols.…”
Section: Introductionmentioning
confidence: 99%